Decadal Response of Mesozooplankton Assemblages to Nutrient Load Reductions in Laizhou Bay, China - Jiang, Huichao; Liu, Dongyan; Ma, Yuanqing; Su, Bo; Liu, Ning; Zhang, Juan; He, Jianlong; Qin, Huawei; Song, Xiukai; Sun, Shan; Xing, Hongyan (Frontiers in Marine Science, 2022)
Nutrient reduction in catchments is an important strategy to mitigate coastal eutrophication. The responses of ecosystems to nutrient reduction on a decadal scale can help us to understand the effects of environmental restoration. Here, the cascading trophic interactions of mesozooplankton and phytoplankton in Laizhou Bay were analyzed to examine the effects of river nutrient reductions during 2004–2014. The results showed that the diversity of the mesozooplankton assemblages and the proportion of higher trophic species increased after nutrient reductions, and mesozooplankton abundance showed obvious decrease annual trends. A significantly positive correlation between mesozooplankton and phytoplankton abundance was identified in August, and mesozooplankton abundance was mainly influenced by phytoplankton abundance in August while by microzooplankton and jellyfish in May when the phytoplankton abundance was lower. This result indicates that the recovery of mesozooplankton assemblages in Laizhou Bay is a slow process after nutrient reductions and might have cascading trophic interactions with phytoplankton recovery.